A longitudinal study of CMT1A using Rasch analysis based CMT neuropathy and examination scores. (3rd March 2020) - Fridman, Vera; Sillau, Stefan; Acsadi, Gyula; Bacon, Chelsea; Dooley, Kimberly; Burns, Joshua; Day, John; Feely, Shawna; Finkel, Richard S.; Grider, Tiffany; Gutmann, Laurie; Herrmann, David N.; et al.
Abstract : Objective: To evaluate the sensitivity of Rasch analysis-based, weighted Charcot-Marie-Tooth Neuropathy and Examination Scores (CMTNS-R and CMTES-R) to clinical progression in patients with Charcot-Marie-Tooth disease type 1A (CMT1A). Methods: Patients with CMT1A from 18 sites of the Inherited Neuropathies Consortium were evaluated between 2009 and 2018. Weighted CMTNS and CMTES modified category responses were developed with Rasch analysis of the standard scores. Change from baseline for CMTNS-R and CMTES-R was estimated with longitudinal regression models. Results: Baseline CMTNS-R and CMTES-R scores were available for 517 and 1, 177 participants, respectively. Mean ± SD age of participants with available CMTES-R scores was 41 ± 18 (range 4–87) years, and 56% were female. Follow-up CMTES-R assessments at 1, 2, and 3 years were available for 377, 321, and 244 patients. A mixed regression model showed significant change in CMTES-R score at years 2 through 6 compared to baseline (mean change from baseline 0.59 points at 2 years, p = 0.0004, n = 321). Compared to the original CMTES, the CMTES-R revealed a 55% improvement in the standardized response mean (mean change/SD change) at 2 years (0.17 vs 0.11). Change in CMTES-R at 2 years was greatest in mildly to moderately affected patients (1.48-point mean change, 95% confidence interval 0.99–1.97, p < 0.0001, for baseline CMTES-R score 0–9). Conclusion: The CMTES-R demonstrates change over time in patients with CMT1A and is more sensitive than the original CMTES. The CMTES-R was most sensitive to change in patients with mild to moderate baseline disease severity and failed to capture progression in patients with severe CMT1A. ClinicalTrials.gov identifier: NCT01193075.